1996
DOI: 10.1074/jbc.271.20.11920
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Creatine Kinases

Abstract: In both mammals and birds, the creatine kinase (CK) family consists of four types of genes: cytosolic brain type (B-CK); cytosolic muscle type (M-CK); mitochondrial ubiquitous, acidic type (Mi a -CK); and mitochondrial sarcomeric, basic type (Mi b -CK). We report here the cloning of the chicken Mi a -CK cDNA and its gene. Amino acid sequences of the mature chicken Mi-CK proteins show about 90% identity to the homologous mammalian isoforms. The leader peptides, however, which are isoenzyme-specifically conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Both phosphotransferases belong to a family that is so highly conserved that functional hybrid enzymes can be formed (Reddy and Watts, 1994). Vertebrates have four CK genes that encode tissue-specific isozymes (Wallimann, 1994;Muhlebach et al, 1996). Although echinoderms and annelids can express both CK and argK (Thoai and Robin, 1964;Moreland et al, 1967), only argK has been reported in arthropods (Wallimann and Eppenberger, 1973).…”
mentioning
confidence: 99%
“…Both phosphotransferases belong to a family that is so highly conserved that functional hybrid enzymes can be formed (Reddy and Watts, 1994). Vertebrates have four CK genes that encode tissue-specific isozymes (Wallimann, 1994;Muhlebach et al, 1996). Although echinoderms and annelids can express both CK and argK (Thoai and Robin, 1964;Moreland et al, 1967), only argK has been reported in arthropods (Wallimann and Eppenberger, 1973).…”
mentioning
confidence: 99%